Räumliche Konzentration, ökonomische Kompetenz und regionale Entwicklung.: Das Beispiel der oberfränkischen Autozulieferindustrie - Schamp, Eike W. (ERDKUNDE, 1997)
Spatial clusters are a general phenomenon in industrial production which has been analyzed intensively both among low-tech, but design-intensive, and high-tech industries. Middle-tech and supplies industries, however, sometimes apply to spatial clustering as well. Increasingly, clusters are explained by dynamic agglomeration economies referring to capabilities in interactive learning and local sources of competence. This article attempts to identify three different realms of competence of firms and establishments: that in R&D, in production procedures and logistics. These competences are increasingly required in the automotive supplies industry which is characterized by dependencies between large and small firms in a quasi-pyramidal form. The conclusion of an empirical analysis in Upper Franconia is that extant competences of firms have grown up during a favourable phase when this area was peripheral to the former Federal Republic of Germany, but that regional institutions as a base for reproducing firm competences have been created too late in order to support firms under the current squeeze from global competition. Hence, this regional production cluster is rather fragile.